Claiming Democracy: The Paris 1968 May Revolts in the Mass Media and Their European Dimensions - Schulz-forberg, Hagen (Cuadernos de Historia Contemporánea, 2009)
The paper explores the existence of a European public sphere drawing upon the example of the Paris 1968 May revolts. Its addresses questions as: How European was 1968 when it happened? And what does European refer to? Is it European already when it happens in more than one European country or city? Can one ignore the influence of the USA and still call it European? Are the European experiences so distinct from the American ones that one can carve out a clear-cut European version of 1968? Why do we ask the question of whether or not 1968 was European when it clearly was one of the crucial events in recent history?